2016
DOI: 10.1159/000446081
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Spin Labeling and Blood Oxygen Level-Dependent MRI Cerebrovascular Reactivity in Cerebrovascular Disease: A Systematic Review and Meta-Analysis

Abstract: Background: The cerebrovascular reactivity (CVR) results of blood oxygen level-dependent (BOLD) and arterial spin labeling (ASL) MRI studies performed in patients with cerebrovascular disease (steno-occlusive vascular disease or stroke) were systematically reviewed. Summary: Thirty-one articles were included. Twenty-three (74.2%) studies used BOLD MRI to evaluate the CVR, 4 (12.9%) studies used ASL MRI and 4 (12.9%) studies used both BOLD and ASL MRI. Thirteen studies (3 significant) found a lower BOLD CVR, 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 79 publications
0
23
0
2
Order By: Relevance
“…Assessment of CVR by breath-holding index of middle cerebral arteries via transcranial doppler ultrasound has found global CVR decreased as the severity of WMH increased and associated with cognitive performance [34]. Findings from BOLD-based CVR studies remain controversial [16]. Some studies reported whole brain CVR was not related to WMH [42,43], but others showed decreased CVR at baseline can predict the process of WMH lesions [18,44,45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of CVR by breath-holding index of middle cerebral arteries via transcranial doppler ultrasound has found global CVR decreased as the severity of WMH increased and associated with cognitive performance [34]. Findings from BOLD-based CVR studies remain controversial [16]. Some studies reported whole brain CVR was not related to WMH [42,43], but others showed decreased CVR at baseline can predict the process of WMH lesions [18,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Impaired CVR is correlated closely with normal aging [13] and might be a sensitive early predictor of Alzheimer's disease [14]. In addition, it is reported that impaired CVR is the most reliable neuroimaging predictor of impending cerebrovascular disease [15,16], and could be a neuroimaging marker guiding the treatment and prevention of stroke and cerebral small vessel disease (CSVD) [17,18]. Furthermore, increasing evidences have demonstrated that CVR function is associated with subtle perfusion and microstructure changes in normal-appearing white matter (NAWM) [19], and has been involved in the pathophysiology disruption of the brain network connectome in individuals with WMH [20].…”
Section: Introductionmentioning
confidence: 99%
“…Further studies are required to investigate whether BOLD and ASL could provide complementary information about ACZ-induced CVR. Simultaneous evaluation of ASL and BOLD, such as with dual-echo ASL (Smeeing et al, 2016), may prove valuable as a synergistic approach for further interrogation. Combining dual-echo ASL imaging and ACZ to characterize CVR is currently underway in our group.…”
Section: Discussionmentioning
confidence: 99%
“…The CVR is the ability of cerebral vessels to dilate or constrict in response to challenges or maneuvers [5,6]. In addition, CVR is thought to be an important index of the brain's vascular health, and provides vascular-reserve information that is complementary to steady-state vascular parameters, including CBF and CBV [7,8]. There have been two main approaches to measuring CVR.…”
Section: Introductionmentioning
confidence: 99%